Prophylactic use of Levofloxacin during induction of acute lymphoblastic leukaemia in children—experience from Pakistan - Rehman, Palwasha; Shaukat, Zunaira; Saeed, Haleema; Raza, Aun; Anjum, Sadia; Muhammad Wali, Rabia (Journal of the Pakistan Medical Association, 2023)
To assess whether prophylactic use of Levofloxacin would reduce the number of febrile neutropenia episodes during the induction phase, a single-centre, case-control study was carried out. Data was collected prospectively of patients who received Levofloxacin prophylaxis during the induction chemotherapy from September 2019 till October 2020. The cases were compared with historical controls who did not receive antibiotics prophylaxis. A total of 121 patients were enrolled, among which 61 patients were cases, whereas 60 patients were controls. The patients who received Levofloxacin prophylaxis had lower rate of febrile neutropenia episodes than patients who did not receive any prophylaxis (P 0.01) (odds ratio [OR] :0.23, CI 95percent). No significant difference in induction mortality was seen between the two groups (p 0.14). Levofloxacin prophylaxis reduced the rate of febrile neutropenia episodes among patients, but it did not affect the infection related mortality. Keywords: Antibiotic Prophylaxis, Acute Lymphoblastic Leukaemia, Children.